The Effect of Competency Based Training (CBT) and Competency Certificate Type on The Ability of Graduates of The Work Training Center (BLK) of Wonogiri District at PT Top N Top - Agung Susila Susila; Budi Santosa; Muhammad Sayuti (Journal of Vocational Education Studies, 2021)
The results showed that: (1) Based on the test, the results of the research proved that the Training Method (X1) proved to have a positive effect on the Work Ability of Training Graduates at UPTD BLK Wonogiri (Y); (2) Based on the test, it turns out that the results of the study prove that the Instructor / Trainer (X2) has no positive effect on the Work Ability of Training Graduates at UPTD BLK Wonogiri (Y); (3) Based on the test, it turns out that the research results prove that the Instructor / Trainer (X3) has a positive effect on the Work Ability of Training Graduates at UPTD BLK Wonogiri; (4) Based on the test, it turns out that the research results prove that the Method of Facilities and Infrastructure (X4) has a positive effect on the Work Ability of Training Graduates at UPTD BLK Wonogiri (Y); (5) Based on the test, it turns out that the research results prove that the certificate (X5) is proven to have a positive effect on the Work Ability of Training Graduates at UPTD BLK Wonogiri (Y); (6) Based on testing simultaneously (Test F), it turns out that the results of the research prove that all variables of Training Methods, Instructors / Trainers, Training Materials and Facilities and Infrastructure as well as certificates together or simultaneously prove to have a positive effect on the factor formation of the variables. Apparel Garment Program Training at UPTD BLK Wonogiri.